PENERAPAN E-LEARNING DALAM INOVASI PENDIDIKAN DI SEKOLAH MAN 2 MODEL MEDAN - Dalimunthe, Danil; Harahap, May Syaroh; Siregar, Sri Intan (Yayasan Pendidikan Islam Akmalia, 2022)
The rapid development of technology and information has affected various aspects of life including in the field of education. Therefore, educational institutions must be able to anticipate the development of Ambut with the imus of menses, using a program that is in accordance with the needs of students. education by implementing e-learning, Electronic Learning, is a new way of teaching and learning that uses electronic media Unternet schoga stem learning Expectations for E-learning systems in the future due to the replacement of E-learning becoming more and more doctive along with the development of technology and buyer methods that E-learning system development is also expected to not only take into account financial day profitability issues, but also to pay attention to the psychological side of students and to accommodate the return and learning centers of each participant. Adan Hun and Melina Mivat to find out how Where is the application of E-Learning in the Invasion of Education in Schools. The research method that the author uses is a qualitative research method with a lecture technique.